Legal Protection for Consumer Safety Due to Inconsistencies in Grab Partner Identities - Chaerul Chafid, Candra; Arifin, Zaenal; Junaidi, Muhammad (Yayasan Studi Cendekia Indonesia (YSCI), 2025)
This study analyses legal protection for consumer safety arising from inconsistencies between the identities of Grab driver partners displayed in the application and those encountered in practice, as well as the legal remedies available when consumer safety and security are not adequately guaranteed. The research employs an empirical juridical approach with qualitative methods, using a case study at PT Grab Indonesia in Semarang City. Data were collected through in-depth interviews, field observations, and document analysis, and analysed descriptively by linking empirical findings with Law Number 8 of 1999 concerning Consumer Protection. The findings reveal that mismatches in partner identities constitute a recurring issue that undermines consumers’ rights to accurate, clear, and honest information, while simultaneously exposing them to heightened safety and security risks. Empirically, consumers experience fear, discomfort, and psychological insecurity during rides, yet often continue the service due to situational constraints, reflecting their weak bargaining position in platform-based service relationships. From the perspective of Gustav Radbruch’s legal theory, these conditions demonstrate deficiencies in legal certainty, justice, and legal utility, particularly regarding platform accountability. This study concludes that effective consumer protection requires not only material compensation, but also guarantees of personal safety, transparent information, and corrective-preventive measures by platform providers. Consumers may pursue layered legal remedies, including internal complaint mechanisms, dispute resolution through the Consumer Dispute Settlement Agency (BPSK), litigation, and criminal reporting in cases involving serious threats or criminal elements.